CUSTOMER SATISFACTION AND BRAND LOYALTY IN THE HOTEL INDUSTRY - Al-Msallam, Samaan (European Scientific Journal, ESJ, 2015)
Most of marketing literature recognizes customer satisfaction as a significant antecedent to Brand loyalty. Further, the relationships between both satisfaction constructs with Brand loyalty have mostly been studied separately. The purpose of this study is to explore the effects of three customer perceptions (brand image, price fairness) on customer satisfaction and Brand loyalty. A combination of a convenience and judgmental sample survey of 584 guests of three different hotels in Damascus was used to the test the hypotheses. The results illustrate that customer satisfaction significantly affects customer loyalty. Also, the factors of brand image and price fairness affect Brand loyalty. Customer perception of brand image and price fairness are almost equally to build up the satisfaction. We suggest that managers should consider price fairness as foundations to build up customer satisfaction, Brand loyalty and, also to improve brand image as an added on value for customers .